(untitled) (The Research of Medical Science Review, 2025)
Introduction: Spontaneous abortion, affecting up to 20% of clinically recognized pregnancies, presents significant clinical challenges. Traditionally managed by uterine evacuation via curettage, recent studies advocate for alternatives like misoprostol, prompting a shift in treatment paradigms. This study investigates outcomes following Manual Vacuum Aspiration (MVA) for early pregnancy loss, contrasting traditional methods with newer approaches. It aims to quantify hospital stay duration, procedure efficacy, and complications such as retained products of conception (RPOC). By addressing gaps in local literature, the study seeks to inform obstetric practice and advance knowledge in managing early pregnancy loss effectively. Objective: To evaluate the outcomes after manual vacuum aspiration in women with early pregnancy loss. Methods: A descriptive case series was conducted at the Department of Obstetrics and Gynaecology, Lady Reading Hospital, Peshawar, from February 26, 2022, to August 26, A total of 222 patients with early pregnancy loss were observed using a non-probability consecutive sampling technique. Outcomes measured included duration of procedure, hospital stay, blood loss, and the incidence of RPOC as detected by ultrasound. Results: The age distribution of the 222 patients showed that 28% were aged 15-20 years, 62% were 21-30 years, and 10% were 31-45 years, with a mean age of 30.6 ± 3.6 years. Weight distribution indicated that 43% weighed 61-70 kg, 45% weighed 71-80 kg, and 12% weighed 81-90 kg, with a mean weight of 70 ± 8.6 kg. Regarding the period of gestation, 61% were between 15-17 weeks and 39% between 18-20 weeks, with a mean gestational age of 18.2 ± 1.5 weeks. The procedure duration was less than 5 minutes in 66% of cases and more than 5 minutes in 34%. Hospital stay was under 24 hours for 72% of patients and over 24 hours for 28%. Blood loss was less than 40 ml in 67% and more than 40 ml in 33% of patients. Retained products of conception were detected in 5.5% of cases. Conclusion: Manual vacuum aspiration is an effective option for managing first-trimester pregnancy losses, demonstrating high efficacy with minimal complications. Further comparisons with other treatment modalities are warranted to solidify its standing in obstetric practice.